Self-propagating high-temperature synthesis (SHS) of porous parts using nanocrystalline NiTi - Goh, Francis Chung Wen (2008)
Porous Nickel Titanium (NiTi) shape memory alloy (SMA) is a promising material for use in applications such as biomedical implants. It has effective damping characteristics to shock by utilizing the energy absorption capabilities. Conventional methods such as the sintering process, hot isostatic pressing (HIP) and spark plasma sintering (SPS) have also been used to produce porous NiTi SMA. However, these methods are generally slow. The self propagation high-temperature synthesis (SHS) process, on the other hand, has been proven to be an ideal alternative in this project, with its rapid processing capability and adaptability in producing materials into cellular/porous structure. In this study, SHS was used to fabricate porous NiTi. The objectives of this study were to achieve nanocrystalline Ni-Ti and investigate the employment of SHS for this. Several process parameters were used to study influence on morphology and reduction of undesirable by-product phases.